Perancangan Media Evaluasi Pembelajaran Berbasis Game Menggunakan Quizwhizzer : Media Evaluasi - Andika Permana, Surya; Musril, Hari Antoni; Derta, Sarwo; Okra, Riri (Yayasan Lembaga Studi Makwa, 2024)
The purpose of this article is to discuss the design of game-based educational evaluation media shown for class VIII SMP N 1 Bukittinggi. The problem faced by Informatics teachers at SMP N 1 Bukittinggi is that the media used in evaluations still use conventional media, namely paper for practice. On the other hand, students feel bored and feel bored, making it difficult for students to do the evaluation given by the teacher and the lack of interest in learning from students so that it affects learning outcomes. This research uses the Research and Development (R&D) method of the GDLC (Game Development Life Cycle) version which is organized into six stages, namely the stages of initiation, pre-production, production, testing, beta and release. The results of this study are proven that the results of the validity test conducted obtained a score of 0.74 and were declared valid, the results of the practicality test obtained a score of 0.91 with a very high category, and the results of the effectiveness test obtained a final score of 0.90 with a high effectiveness category. The impact of this research is that the learning process of students is more focused in the learning atmosphere so that students' understanding of the material increases. Abstrak Tujuan artikel ini adalah untuk membahasa perancangan media evaluasi pendidikan berbasis game yang ditunjukkan untuk kelas VIII SMP N 1 Bukittinggi. Persoalan yang dihadapi guru Informatika di SMP N 1 Bukittinggi bahwa media yang digunakan dalam evaluasi masih menggunakan media konvensional yaitu kertas untuk latihan. Disisi lain peserta didik merasa jenuh dan merasa bosan, sehingga menyulitkan siswa dalam melakukan evaluasi yang diberikan oleh guru dan kurangnya minat belajar peserta didik sehingga berpengaruh kepada hasil belajar. Penelitian ini menggunakan metode Research and Development (R&D) versi GDLC (Game Development Life Cycle) yang disusun dalam enam tahapan, yaitu tahapan initiation, pre-production, production, testing, beta dan release. Hasil penelitian ini dibuktikan bahwah hasil uji validitas yang dilakukan mendapatkan skor 0,74 dan dinyatakan valid, hasil dari uji praktikalitas mendapatkan nilai 0,91 dengan kategori sangat tinggi, dan hasil dari uji efektivitas didapatkan nilai akhir 0,90 dengan kategori efektivitas tinggi. Dampak penelitian ini, proses pembalajaran siswa semakin fokus dalam suasana belajar sehingga pemahaman siswa terhadap materi semakin meningkat.